Penilaian Kelayakan Finansial Terhadap Kebijakan Penjualan Kredit - Lau, Elfreda Aplonia (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2021)
The goal of Company activities in general are for profit. This profit can be received if the acceptance exceeds the sacrifice to get that acceptance. Usualy acceptance obtained from the sale of products in the form of goods or services. This research is focused on selling products in the form of goods that can be done on credit. Credit sales made require financial feasibility responsibilities that provide sales guarantees because the credit sales policy is adopted to obtain an increase in sales volume and profits so it is deemed necessary to be reviewed. Using the theory of finance which focuses on additional net benefits,this research was run. The analytical tool used is descriptive analysis which shows additional net benefits as a basis for determining whether or not the sales policy is feasible.This study shows that the sales policy is considered feasible if there are additional benefits or positive net benefits. Credit sales policy is deemed inappropriate if there is a decrease in net benefits or negative net benefits. Additional net benefits are obtained from the difference between the benefits and the costs associated with the credit increase.